Genetics of Pakistani populations in an Asian and global context - Mehdi, S. Qasim (Henry Stewart Talks, 2007)
Population genetics, Pakistan and south west Asia, Human migrations, DNA markers, Alu repeats, SNPs and STRs, Y chromosome, mitochondrial DNA and HLA markers unravel genetic relationships among populations in Asia and Pakistan